Chiropractic care for hypertension: Review of the literature and study of biological and genetic bases - Sullivan, Stephanie GB; Paolacci, Stefano; Kiani, Aysha Karim; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Hypertension is a multifactorial condition that is among the leading causes of mortality worldwide. Regulation of blood pressure greatly depends upon the activity of the autonomic nervous system. Alterations in the autonomic nervous system can lead to hypertension. In addition to nervous system control and individual physiologic state, various genes can directly influence autonomic responses. The complexity of blood pressure control is reflected in the 20-30% of individuals resistant to traditional pharmacological treatment, this indicates the need for alternative interventions. This article provides an integrative review and discussion of the key neurophysiologic and genetic factors that contribute to blood pressure regulation, the autonomic nervous system (ANS) and manual therapy literature, and the manual therapy and blood pressure literature. Methods: To assess the effects of chiropractic on the management of hypertension we searched articles published from 1980 to 2019 in PubMed, the Index to Chiropractic Literature and CINAHL, using the keywords: chiropractic, spinal manipulation, hypertension, and blood pressure. Results: We found 38 original studies that analyzed the effect of chiropractic therapy on hypertension. Of these studies, 10 were case reports and the statistical significance of the effects of chiropractic on blood pressure was not evaluated on these articles, so we focused on the remaining 28 articles. Conclusions: The results of the review relative to chiropractic care were promising, but often contradictory, suggesting more research should be done. In consideration of the complexity of ANS blood pressure control, an evaluation of patient presenting physiologic and genetic characteristics is recommended and could provide valuable insight relative to the likelihood of patient blood pressure related responsiveness to care